2020
DOI: 10.5327/z2176-947820200675
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of knowledge about stemflow: a systematic review

Abstract: A importância do escoamento pelo tronco para a hidrologia e biogeoquímicados ecossistemas florestais é destacada pelo crescente interesse dacomunidade científica desde os anos 1970. Para resumir as principaiscontribuições dos estudos de escoamento pelo tronco (Sf) dos últimos anos,este trabalho apresenta uma revisão sistemática da literatura, incluindo375 publicações científicas de 2006 e 2019. O Sf em arbustos demonstrouuma eficiência superior (11,1%) ao escoamento pelo tronco em espéciesarbóreas (3,6%). Galh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Stemflow has historically been considered to be a minor component of forest canopy water budgets compared with throughfall, and it was neglected in early studies of forest water and nutrient balances (Llorens and Domingo, 2007). Tonello et al (2021) summarized the main contributions of stemflow (SF) studies from recent years through a systematic review of the literature, including 375 scientific articles published between 2006 and 2019. The authors identified that few studies have related the stemflow effects in biogeochemical cycle more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Stemflow has historically been considered to be a minor component of forest canopy water budgets compared with throughfall, and it was neglected in early studies of forest water and nutrient balances (Llorens and Domingo, 2007). Tonello et al (2021) summarized the main contributions of stemflow (SF) studies from recent years through a systematic review of the literature, including 375 scientific articles published between 2006 and 2019. The authors identified that few studies have related the stemflow effects in biogeochemical cycle more broadly.…”
Section: Introductionmentioning
confidence: 99%